Veronicastrum axillare Alleviates Lipopolysaccharide-Induced Acute Lung Injury via Suppression of Proinflammatory Mediators and Downregulation of the NF-κB Signaling Pathway - Quanxin Ma; Kai Wang; Qinqin Yang; Shun Ping; Weichun Zhao; Qiyang Shou; Weimin Zhou; Minli Chen (Mediators of Inflammation)
Veronicastrum axillare is a traditional medical plant in China which is widely used in folk medicine due to its versatile biological activities, especially for its anti-inflammatory effects. However, the detailed mechanism underlying this action is not clear. Here, we studied the protective effects of V. axillare against acute lung injury (ALI), and we further explored the pharmacological mechanisms of this action. We found that pretreatment with V. axillare suppressed the release of proinflammatory cytokines in the serum of ALI mice. Histological analysis of lung tissue demonstrated that V. axillare inhibited LPS-induced lung injury, improved lung morphology, and reduced the activation of nuclear factor-κB (NF-κB) in the lungs. Furthermore, the anti-inflammatory actions of V. axillare were investigated in vitro. We observed that V. axillare suppressed the mRNA expression of interleukin-1β (IL-1β), IL-6, monocyte chemotactic protein-1 (MCP-1), cyclooxygenase-2 (COX-2), and tumor necrosis factor-α (TNF-α) in RAW264.7 cells challenged with LPS. Furthermore, pretreatment of V. axillare in vitro reduced the phosphorylation of p65 and IκB-α which is activated by LPS. In conclusion, our data firstly demonstrated that the anti-inflammatory effects of V. axillare against ALI were achieved through downregulation of the NF-κB signaling pathway, thereby reducing the production of inflammatory mediators.